Green adsorbents to remove metals, dyes and boron from polluted water - Inamuddin 1980-; Ahamed, Mohd Imran; Lichtfouse, Eric 1960-; Asiri, Abdullah Mohamed 1966- (Environmental chemistry for a sustainable world, 2021)
This book reviews adsorption techniques to clean wastewater, with focus on pollution by dyes and heavy metals. Advanced adsorbents include carbon nanomaterials, biomass, cellulose, polymers, clay, composites and chelating materials